Messianic time, settler colonial technology and the elision of Palestinian presence in Jerusalem's historic basin. (May 2020) - Busbridge, Rachel
Abstract: Advancing the settler colonial paradigm through a temporal perspective on territoriality, this article argues that the Jewish messianic idea is a distinctive feature of Israeli settler colonialism and an important element of Zionist territorial production. Specifically, the article contends that messianic time constitutes a specific settler colonial technology of domination which finds place-based expression in the 'historic basin' of occupied East Jerusalem. This is illustrated through two sites: the City of David archaeological park in the Palestinian village of Silwan and the Temple Mount/Haram al-Shariff, current home of the Dome of the Rock and prophesised location of the Third Jewish Temple. Both are at the frontier of settlement in the historic basin and the messianic conception of a mythical past and redemptive future aids claims to territorial exclusivity by 'disappearing' Palestinians in the present. The article concludes by reflecting on the value of an analytical focus on time for settler colonial scholarship on Israel-Palestine and in political geography more broadly.